2014
DOI: 10.1371/journal.pone.0104340
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Genetics of the Philippine Tarsier: Cryptic Genetic Variation Restructures Conservation Priorities for an Island Archipelago Primate

Abstract: Establishment of conservation priorities for primates is a particular concern in the island archipelagos of Southeast Asia, where rates of habitat destruction are among the highest in the world. Conservation programs require knowledge of taxonomic diversity to ensure success. The Philippine tarsier is a flagship species that promotes environmental awareness and a thriving ecotourism economy in the Philippines. However, assessment of its conservation status has been impeded by taxonomic uncertainty, a paucity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 43 publications
(46 reference statements)
1
23
0
Order By: Relevance
“…Recent studies aimed at resolving species complexes have identified cryptic genetic diversity and important evolutionary units thereby clarifying these species’ taxonomy and conservation status (e.g., Welton et al 2009; 2010; Sanguila et al 2011; Linkem and Brown 2013). Such studies have confirmed the importance of using of multiple sources of data for a sound understanding of species complexes (Brown and Guttman 2002; Grismer et al 2013; Welton et al 2013a, 2013b; Brown et al 2014; Siler et al 2014ad). …”
Section: Discussionmentioning
confidence: 63%
“…Recent studies aimed at resolving species complexes have identified cryptic genetic diversity and important evolutionary units thereby clarifying these species’ taxonomy and conservation status (e.g., Welton et al 2009; 2010; Sanguila et al 2011; Linkem and Brown 2013). Such studies have confirmed the importance of using of multiple sources of data for a sound understanding of species complexes (Brown and Guttman 2002; Grismer et al 2013; Welton et al 2013a, 2013b; Brown et al 2014; Siler et al 2014ad). …”
Section: Discussionmentioning
confidence: 63%
“…The group includes many endangered species, and surveying genetic diversity in this group is crucial to their conservation. However, studies conducted to date have largely been restricted to mitochondrial DNA and microsatellites (e.g., Blair et al, 2014;Brown et al, 2014). Transcriptome data revealed relatively high genetic diversity in this group compared to Simian primates, with the exception of aye-ayes (Daubentonia madagascariensis; π ≈ 7.2 × 10 −4 ), whose genetic diversity was found to be similar to or lower than non-African humans (Perry et al, 2012).…”
Section: Prosimians (Lemuriformes and Tarsiiformes)mentioning
confidence: 95%
“…In Madagascar, illicit gold and sapphire mining by itinerant miners has affected many forests, including protected ones ( 19 ). Mining of gold, nickel, and copper on Dinagat island, in the Philippines, is endangering the survival of the Philippine tarsier ( Carlito syrichta ) ( 20 ). Bushmeat hunting associated with the mining of coltan, tin, gold, and diamonds in the DRC is the main threat to Grauer’s gorilla ( G. beringei graueri ) ( 21 ); recent surveys indicate a 77% decline in its numbers, from 17,000 in 1995 to just 3800 in 2014/2015 ( 22 ).…”
Section: Factors That Threaten Primate Populationsmentioning
confidence: 99%